Pengaruh Stimulasi Visual Untuk Meningkatkan Kemampuan Membaca Pada Anak Disleksia - Kawuryan, Fajar; Raharjo, Trubus (Jurnal Psikologi: PITUTUR, 2012)
This study aimed to investigate the influence of visual stimulation on the ability of dyslexic children to read in elementary school. The research was conducted in SD 2 and SD 3  rotten Holy Bae District. The sample inthis  study  were  students  in  the  category  of  children  as  dyslexic  children (reading disorder). The sample in this study amounted to 21 students. This research  uses  experimental  research  by  providing  treatment  to  students through visual stimulation using a one group pre test-post test design. Data processing results show t1.2 different coefficient of 3.141 with a p = 0.005 (p <0.05). It is also indicated by the mean difference in both the average  post-test  data  reading  skills  of  elementary  students  are  dyslexic 170.910 retata higher than pre test data reading skills of elementary school students  are  dyslexic  of  90.173.  These  results  indicate  that  there  is  a significant  difference  between  pre  test  and  post  test  of  students´  reading ability  of  dyslexic  SD  before  and  after  treatment  with  visual  stimulation. Based  on  the  results  of  data  analysis  showed  no  differences  in  reading ability  before  and  after  visual  stimulation  treatment  in  children  with dyslexia,  in  which  the  reading  skills  of  elementary  school  students  that dyslexia is given higher after treatment than before treatment is given.